'It sounds like a great idea but…': a qualitative study of GPs' attitudes towards the development of a national diabetes register. Issue 11 (18th July 2014) - Mc Hugh, Sheena M; O'Mullane, Monica; Perry, Ivan J; Bradley, Colin
Abstract : Objective: The aim of this study was to investigate the attitudes of general practitioners (GPs) to the development of a national diabetes register as a way of improving the quality of care. Design: Qualitative study using semistructured interviews. Setting: General practice, Ireland. Participants: Purposive sample of 29 GPs and two practice nurses. Participants' practices varied by (a) location (rural/urban), (b) size (single-handed/group practice) and (c) extent of computerisation. Methods: The semistructured topic guide focused on experiences of change in the health system at a local and national level and attitudes towards the development of a national diabetes register. Analysis was conducted using the Framework approach. Results: Participants were sceptical about the development of a national diabetes register. The main advantage was 'knowing the numbers' for epidemiological and policy purposes. However, participants questioned the benefits for their practice and patients. There were concerns that it would drain resources from other priorities and distract from patient management. These attitudes were strongly influenced by previous experience of change in the health system. Participants felt that remuneration would be necessary to ensure full engagement, reflecting wider frustrations with payment structures for general practice. There was a sense of wariness towards health service administration which was not specific to diabetes care but which coloured some participants' attitudes towards a national register. In contrast, participants referred to positive experiences of change at a local level, facilitated by a 'practice ethos' and professional leadership. Conclusions: This study highlights the growing sense of scepticism and inertia towards change within the health system. This inertia stems from previous experience and the competing demands of maintaining versus improving care in a system with dwindling resources.